Profile of women with retained placenta at a tertiary care hospital - Gaddameedi Sai Maheswari; Sangeeta Shah; Rani Kumari; Mamidi Rachana (MRIMS Journal of Health Sciences)
The placenta is said to be retained when it is not expelled from the uterus even 30 min after the delivery of the baby. The occurrence of retained placenta following vaginal birth is estimated to be 1%–3% of deliveries. It can lead to severe bleeding, infection, and other adverse outcomes, making it a significant concern in obstetric care. Hence, the present study was carried out to study the profile of women with retained placenta. This was a descriptive study among 97 women with retained placenta. The incidence of retained placenta was 97 (1.8%). The most common characteristic feature was postdated pregnancy in 29.8%. Eighty women responded to medical management alone, whereas 17 women required manual removal. The most common complication was postpartum hemorrhage in 33.3%. We conclude that a retained placenta can be a source of significant hemorrhagic and surgical morbidity to the mother. In considering ways to lessen morbidity, the clinician should have a knowledge of the clinical profile of retained placenta.